ANALYSIS OF MARRIAGE DISPENSATION CASE DECISIONS IN BOGOR REGENCY: REVIEW OF LAW AND SOCIAL ASPECTS - Purbayu, Faisal; Sutisna, Sutisna; Hambari, Hambari (IBN KHALDUN BOGOR, 2024)
Marriage dispensation is a complex issue that raises questions regarding the legal and social aspects of it. This research explores marriage dispensation decisions in Bogor Regency, by taking a case study from the Cibinong Class 1 A Religious Court. The analytical method includes legal and social approaches to understand the factors that influence marriage dispensation decisions. Through a normative juridical approach, this research identifies the legal basis underlying marriage dispensation decisions, exploring the legal criteria and considerations used by the Cibinong Class 1 A Religious Court. In addition, a sociologicalapproach is used to uncover the social impact of dispensation decisions, including the role of society and norms that influence the judicial process. Results This research provides an in-depth understanding of how the justice system, especially at the Cibinong Religious Court, handles marriage dispensation cases. Findings suggest that marriage dispensation decisions are influenced by a combination of legal factors and social considerations, paying particular attention to the dissatisfaction and stability of the marital relationship. This research has the potential to provide a more holistic view of the problem of marriage dispensation at the local level, especially in Bogor Regency. The implications of the findings can help improve policies at the regional level and provide a basis for a better understanding of the balance between legal and social aspects in handling marriage dispensation cases.